Coomaniella (Coomaniella) janka sp. nov. from China (Coleoptera: Buprestidae) - Jendek, Eduard (Zootaxa, 2005)
Coomaniella (Coomaniella) janka sp. nov. from China, Henan province, is described. This species belongs to the Coomaniella macropus species group with a close relation to Coomaniella (Coomaniella) lao Jendek & Kalashian, 1999.